Hubungan Indeks Massa Tubuh Dengan Keseimbangan Dinamis Pada Lanjut Usia - Aisia Hafza (2021)
Background: Elderly is a process of slowly disappearing the ability of tissues to repair, replace, maintain proper structure and function so they do not survive a disease. As people age, their will be changes in body mass index due to illness or because of energy intake that enters the body. The body's spends more than ther energy expended such as rarely exercise so that the calories are converted in to fat wich cause the body mass index to be came ubnormal. This studie aims to determine whetheir there is a realitionship between body mass index and dynamic balance in elderly. Design of the final scientivic papper study is cross sectional with descriptive correlative design. The sample used in this study where the elderly in Kalimatunsawa Indonesia Foundation located in Bekasi with a total of 48 people while the parameters used are body mass index to measure the condition of the body whether its classified as not overweight or overweight, then using the time up and go test to measure dynamic balance, Result: this study used SPSS 25, the correlation coefficient was optained using the spearman's rho test with time up and go value of p=1 and body mass index value of p= -0,152. Besed on these result, it can be concluded that there is no significan relationship between body mass index and dynamic balance in elderly.